Recruitment and retention of participants in longitudinal studies after a natural disaster. (April 2022) - McLeod, Geraldine F.H.; Horwood, L. John; Darlow, Brian A.; Boden, Joseph M.; Martin, Julia; Spittlehouse, Janet K.; Carter, Frances A.; Jordan, Jennifer; Porter, Richard; Bell, Caroline; Douglas, Katie; Henderson, Jacki; et al.
Abstract : Climate change and population growth will increase vulnerability to natural and human-made disasters or pandemics. Longitudinal research studies may be adversely impacted by a lack of access to study resources, inability to travel around the urban environment, reluctance of sample members to attend appointments, sample members moving residence and potentially also the destruction of research facilities. One of the key advantages of longitudinal research is the ability to assess associations between exposures and outcomes by limiting the influence of sample selection bias. However, ensuring the validity and reliability of findings in longitudinal research requires the recruitment and retention of respondents who are willing and able to be repeatedly assessed over an extended period of time. This study examined recruitment and retention strategies of 11 longitudinal cohort studies operating during the Christchurch, New Zealand earthquake sequence which began in September 2010, including staff perceptions of the major impediments to study operations during/after the earthquakes and respondents' barriers to participation. Successful strategies to assist recruitment and retention after a natural disaster are discussed. With the current COVID-19 pandemic, longitudinal studies are potentially encountering some of the issues highlighted in this paper including: closure of facilities, restricted movement of research staff and sample members, and reluctance of sample members to attend appointments. It is possible that suggestions in this paper may be implemented so that longitudinal studies can protect the operation of their research programmes.